Efflux-mediated fluoroquinolone resistance in the multidrug-resistant Pseudomonas aeruginosa clinical isolate PA7: identification of a novel MexS variant involved in upregulation of the mexEF-oprN multidrug efflux operon - Morita, Yuji; Tomida, Junko; Kawamura, Yoshiaki (Frontiers in Microbiology, 2015)
The emergence of multidrug-resistant Pseudomonas aeruginosa has become a serious problem in medical settings. P. aeruginosa clinical isolate PA7 is resistant to fluoroquinolones, aminoglycosides, and most -lactams but not imipenem. In this study, enhanced efflux-mediated fluoroquinolone resistance of PA7 was shown to reflect increased expression of two resistance nodulation cell division (RND) -type multidrug efflux operons, mexEF-oprN and mexXY-oprA. Such a clinical isolate has rarely been reported because MexEF-OprN-overproducing mutants often increase susceptibility to aminoglycosides apparently owing to impairment of the MexXY system. A mutant of PA7 lacking three RND-type multidrug efflux operons (mexAB-oprM, mexEF-oprN, and mexXY-oprA) was susceptible to all anti-pseudomonas agents we tested, supporting an idea that these RND-type multidrug efflux transporters are molecular targets to overcome multidrug resistance in P. aeruginosa. mexEF-oprN-upregulation in P. aeruginosa PA7 was shown due to a MexS variant harboring the Valine-155 amino acid residue. This is the first genetic evidence shown that a MexS variant causes mexEF-oprN-upregulation in P. aeruginosa clinical isolates.